Method for manufacturing multi-layer container
By adjusting the water content and composition of the PA layer in dual-axis stretching blow molding of PET and PA layers, the method addresses interlayer delamination in multilayer containers, improving mechanical properties and durability.
Patent Information
- Application Number
- CN202080070335.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-10-08
- Filing Date
- 2020-09-25
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2040-09-25
AI Technical Summary
Multilayer containers composed of layers formed by polyethylene terephthalate (PET) and polyamide (PA) often experience interlayer delamination due to differences in thermal expansion and stress accumulation during the manufacturing process.
The method involves pre-forming bilayer sheets of PET and PA through dual-axis stretching blow molding, adjusting the water content and composition of the PA layer to ensure a specific storage modulus (G') and water content, thereby reducing interlayer delamination.
This approach enhances the impact resistance and prevents interlayer delamination by optimizing the mechanical properties of the PA layer, ensuring a stable and durable multilayer container.
Smart Images

Figure CN114555354B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing a multi-layer container. Background Art
[0002] Conventionally, multilayer bodies and multilayer containers using polyester resin as resins constituting outer and inner layers and having a polyamide resin layer (barrier layer) formed of polyamide resin between the outer and inner layers have been studied (Patent Documents 1 and 2).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2016-198911
[0006] Patent Document 2: Japanese Patent Application Publication No. 2007-210209 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] However, the present inventors have conducted studies and found that interlayer delamination may occur in a multilayer container having a layer formed of a polyester resin and a polyamide resin layer formed of a polyamide resin.
[0009] The present invention aims to solve the above-mentioned problems and provides a method for producing a multilayer container having a layer mainly composed of a polyester resin and a layer mainly composed of a polyamide resin, and in which interlayer delamination is less likely to occur.
[0010] Solutions for solving problems
[0011] Based on the above-mentioned problems, the inventors conducted research and found that when manufacturing a multi-layer container, the preform is subjected to biaxial stretch blow molding, the storage modulus G' of the polyamide resin during the aforementioned biaxial stretch blow molding is set to a specific range, the moisture content of the polyamide resin layer of the preform before biaxial stretch blow molding is adjusted, and a specified polyamide resin is used, thereby solving the above-mentioned problems.
[0012] Specifically, the above-mentioned problems were solved by the following means.
[0013] <1> A method for manufacturing a multi-layer container, comprising the steps of: biaxially stretching and blow-molding a preform having a layer mainly composed of a polyester resin and a layer mainly composed of a polyamide resin,
[0014] The storage modulus G' of the polyamide resin obtained by measuring the dynamic viscoelasticity of the preform at a temperature and a frequency of 1 Hz during the biaxial stretch blow molding is 1 MPa or more and less than 100 MPa,
[0015] The water content of the layer containing the polyamide resin as a main component in the preform immediately before the biaxial stretch blow molding is 0.5% or less,
[0016] The polyamide resin includes the following xylylenediamine-based polyamide resin: composed of structural units derived from diamine and structural units derived from dicarboxylic acid, 70 mol% or more of the structural units derived from diamine are derived from meta-xylylenediamine, 80 to 97 mol% of the structural units derived from dicarboxylic acid are derived from α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 8 carbon atoms, and 20 to 3 mol% are derived from aromatic dicarboxylic acid (wherein the total of the structural units derived from α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 8 carbon atoms and the structural units derived from aromatic dicarboxylic acid does not exceed 100 mol%).
[0017] <2> according to <1> In the method for producing a multi-layer container, the heating temperature of the preform during the biaxial stretch blow molding is not less than the glass transition temperature of the polyamide resin and not more than 115°C.
[0018] <3> according to <1> or <2> The method for manufacturing a multi-layer container, wherein the storage modulus G' is 5 to 30 MPa.
[0019] <4> according to <1> or <2> The method for manufacturing a multi-layer container, wherein the storage modulus G' is 15 to 30 MPa.
[0020] <5> according to <1> ~ <4> The method for producing a multi-layer container according to any one of the preceding claims, wherein the water content is 0.1 to 0.45%.
[0021] <6> according to <1> ~ <4> The method for producing a multi-layer container according to any one of the preceding claims, wherein the water content is 0.1 to 0.34%.
[0022] <7> according to <1> ~ <6> The method for producing a multi-layer container according to any one of the preceding claims, wherein the polyester resin is composed of structural units derived from a glycol and structural units derived from a dicarboxylic acid, 70 mol% or more of the structural units derived from the dicarboxylic acid are derived from at least one selected from terephthalic acid and esters thereof, and 70 mol% or more of the structural units derived from the glycol are derived from ethylene glycol.
[0023] <8> according to <1> ~ <7> The method for producing a multi-layered container according to any one of the preceding claims, wherein at least one of the polyamide resins is an amorphous resin.
[0024] <9> according to <1> ~ <8> The method for producing a multi-layer container as described in any one of the preceding claims, wherein the polyamide resin further comprises an amorphous polyamide resin (excluding the xylylenediamine-based polyamide resin),
[0025] The ratio of the xylylenediamine polyamide resin to the amorphous polyamide resin (excluding the xylylenediamine polyamide resin) is as follows: 40 to 5 parts by mass of the amorphous polyamide resin relative to 60 to 95 parts by mass of the xylylenediamine polyamide resin.
[0026] <10> according to <1> ~ <9> The method for producing a multi-layer container according to any one of the preceding claims, wherein in the xylylenediamine-based polyamide resin, the α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 8 carbon atoms is adipic acid, and the aromatic dicarboxylic acid is isophthalic acid.
[0027] <11> according to <1> ~ <10> The method for manufacturing a multi-layer container as described in any one of the above, further comprises the step of manufacturing the aforementioned preform, including the step of adjusting the moisture content of the aforementioned manufactured preform.
[0028] <12> according to <11> The method for manufacturing a multi-layer container comprises storing the manufactured preform in a moisture-proof state to adjust the moisture content.
[0029] <13> according to <1> ~ <12> The method for producing a multi-layer container according to any one of the preceding claims, wherein the preform further comprises a layer having a second polyester resin as a main component,
[0030] The layer containing the polyester resin as a main component, the layer containing the polyamide resin as a main component, and the layer containing the second polyester resin as a main component are stacked in this order.
[0031] Effects of the Invention
[0032] A method for producing a multilayer container having a layer mainly composed of a polyester resin and a layer mainly composed of a polyamide resin, and a method for producing a multilayer container in which interlayer delamination is unlikely to occur, can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a schematic diagram showing the manufacturing process of the multi-layer container of the present invention. DETAILED DESCRIPTION
[0034] Hereinafter, the content of the present invention will be described in detail. It should be noted that in the present specification, "to" is used to mean that the numerical values described before and after it are included as the lower limit and the upper limit.
[0035] In this specification, various physical property values and characteristic values are those at 23° C. unless otherwise specified.
[0036] The method for producing a multi-layer container in the present invention is characterized in that it comprises the steps of: biaxially stretching and blow molding a preform having a layer having a polyester resin as a main component (hereinafter, sometimes referred to as a "polyester resin layer") and a layer having a polyamide resin as a main component (hereinafter, sometimes referred to as a "polyamide resin layer"), wherein the storage modulus G' of the polyamide resin obtained by measuring the dynamic viscoelasticity of the preform at a temperature and a frequency of 1 Hz during the biaxially stretching and blow molding is 1 MPa or more and less than 100 MPa, that is, the polyamide resin as a main component in the preform before the biaxially stretching and blow molding is The moisture content of the layer of the main component is 0.5% or less, and the above-mentioned polyamide resin includes the following xylylenediamine-based polyamide resin: composed of structural units derived from diamine and structural units derived from dicarboxylic acid, 70 mol% or more of the above-mentioned structural units derived from diamine are derived from meta-xylylenediamine, 80 to 97 mol% of the above-mentioned structural units derived from dicarboxylic acid are derived from α, ω-straight-chain aliphatic dicarboxylic acid having 4 to 8 carbon atoms, and 20 to 3 mol% are derived from aromatic dicarboxylic acid (wherein the total of the structural units derived from α, ω-straight-chain aliphatic dicarboxylic acid having 4 to 8 carbon atoms and the structural units derived from aromatic dicarboxylic acid does not exceed 100 mol%).
[0037] By making the storage modulus G' of the polyamide resin equal to or greater than the above lower limit, the residual stress generated in the container during biaxial stretch blow molding can be increased. As a result, the resistance to stress such as impact / load on the outside of the obtained multilayer container becomes higher, and interlayer delamination between the polyamide resin layer and the polyester resin layer can be suppressed. In addition, by making the storage modulus G' equal to or less than the above upper limit, excessive stress can be applied, and interlayer delamination due to shrinkage of the polyamide layer can be suppressed.
[0038] Furthermore, it is estimated that in the present invention, by setting the water content of the polyamide resin layer to 0.5% or less, the polyamide resin can be molded into a container without reducing the storage modulus G' of the polyamide resin during biaxial stretch blow molding, and interlayer delamination can be more effectively suppressed.
[0039] Here, "before biaxial stretch blow molding" refers to a stage in which a preform produced by an injection molding machine and stored as needed is placed in a biaxial stretch blow molding machine for biaxial stretch blow molding. Also, "during biaxial stretch blow molding" refers to a stage in which a preform is heated to a predetermined temperature, placed in a mold, and biaxial stretch blow molding is performed.
[0040] The storage modulus G' obtained by measuring the dynamic viscoelasticity of the preform at a temperature and a frequency of 1 Hz of the polyamide resin contained in the polyamide resin layer during biaxial stretch blow molding is 1 MPa or more and less than 100 MPa. The lower limit of the storage modulus G' is preferably 5 MPa or more, more preferably 8 MPa or more, further preferably 10 MPa or more, and further preferably 15 MPa or more. In addition, the upper limit of the storage modulus G' is preferably 70 MPa or less, more preferably 50 MPa or less, further preferably 30 MPa or less, and can be 25 MPa or less.
[0041] The storage modulus G′ when the polyamide resin layer contains two or more types of polyamide resins is a measured value obtained by measuring using a sample produced in a state where the polyamide resins are mixed.
[0042] The storage modulus G' is measured by the method described in Examples described later.
[0043] The moisture content of the layer containing the polyamide resin as the main component of the preform immediately before the biaxial stretch blow molding is 0.5% or less. The upper limit of the moisture content is preferably 0.45% or less, more preferably 0.4% or less, further preferably 0.34% or less, and still more preferably 0.31% or less. The lower limit of the moisture content is preferably 0, but 0.1% or more, 0.2% or more is also sufficiently practical.
[0044] When the preform has two or more layers containing a polyamide resin as a main component, at least one layer only needs to satisfy the above-mentioned moisture content, and preferably all layers containing a polyamide resin as a main component satisfy the above-mentioned moisture content.
[0045] The moisture content of the layer containing the polyamide resin as a main component of the preform is measured by the method described in Examples described later.
[0046] Below, according to Figure 1 An example of an embodiment of the method for producing a multilayer container of the present invention will be described. However, the method for producing a multilayer container of the present invention is not limited to Figure 1 The composition recorded in .
[0047] The multilayer container of the present invention is produced by biaxially stretching and blow molding a preform. The multilayer container of the present invention is usually molded by a cold parison molding method.
[0048] Cold parison molding (two-stage molding) is a molding method in which the preform after injection molding is cooled to room temperature and stored, then reheated in another device and supplied to blow molding.
[0049] Figure 1First, a preform is produced to have a desired moisture content ( Figure 1 (1)). The moisture content of the preform 1 is preferably adjusted to the above-specified range at the time of storage before biaxial stretch blow molding or during transfer from the preform molding device to the blow molding device. That is, the method for manufacturing a multilayer container in the present invention preferably includes the following steps: before the preform is supplied to the biaxial stretch blow molding, the moisture content of the preform is adjusted. Specifically, the moisture content is preferably adjusted by storing the preform in a moisture-proof state. Specifically, the following means can be adopted: by storing the preform in a moisture-proof package, storing the preform in a drying room, or drying the preform. In addition, the moisture content of the raw resin can also be adjusted.
[0050] Next, the preform 1 is heated ( Figure 1 (2)). Heating is performed using an infrared heater 2 or the like.
[0051] In the present invention, the heating temperature of the preform during biaxial stretch blow molding is preferably not less than the glass transition temperature (Tg) of the polyamide resin contained in the polyamide resin layer and not more than 115° C. By setting it in the above range, the transparency of the obtained multilayer container is further improved, and there is a tendency that the resistance to interlayer delamination is also further improved.
[0052] The heating temperature of the preform is preferably Tg+2°C or higher, more preferably Tg+5°C or higher. More specifically, it is preferably 90°C or higher, more preferably 95°C or higher, and further preferably 99°C or higher, and may be 100°C or higher, or 102°C or higher. In addition, the upper limit of the heating temperature of the preform is preferably Tg+25°C or lower, more preferably Tg+20°C or lower. More specifically, it is more preferably 112°C or lower, and may be 110°C or lower, or 107°C or lower.
[0053] Next, the heated preform is supplied to the biaxial stretch blow molding. Figure 1 (3)), while stretching by the stretching rod 4, biaxial stretch blow molding is performed ( Figure 1(4) and (5)). As a stretching method, for example, there is a method in which the surface of the preform is heated and then stretched in the axial direction by mechanical means of inserting and pressing with a core rod, and then, high-pressure air of 2 to 4 MPa is usually blown to stretch in the transverse direction and perform blow molding. In addition, in order to improve the heat resistance of the container, the crystallinity of the preform can also be increased. For example, there is a method in which the surface of a multilayer preform is heated and then blow-molded in a mold at a temperature above the glass transition point (single blow molding). Furthermore, it can also be so-called double blow molding, which includes the following steps: a primary blow molding step of biaxially stretching and blow molding the preform larger than the final shape; a step of heating the primary blow-molded product to cause it to shrink by heat and mold it into a secondary intermediate molded product; and, finally, a secondary blow molding step of blow molding the secondary intermediate molded product into the final container shape. The temperature during blow molding is preferably 90 to 120°C, more preferably 95 to 115°C. In relation to Tg of the polyamide resin, it is preferably Tg or higher and Tg+20° C. The temperature during blow molding refers to the temperature at the stage when the preform passes through the heating zone of the blow molding machine and the heating is completed.
[0054] After blow molding, the mold 3 is removed to obtain a multilayer container 5 ( Figure 1 (6)).
[0055] In addition, regarding the method for manufacturing a multi-layer container in the present invention, without departing from the gist of the present invention, reference may be made to paragraphs 0070 to 0074 of Japanese Patent Publication No. 2016-198912, paragraphs 0085 to 0119 of Japanese Patent Publication No. 2016-169027, and the description of Japanese Patent Publication No. Sho 60-232952, and these contents may be incorporated into this specification.
[0056] Next, the preform used in the manufacturing method of the present invention is described. The preform used in the present invention has a layer having a polyester resin as a main component (polyester resin layer) and a layer having a polyamide resin as a main component (polyamide resin layer) as described above. The preform also has a layer having a second polyester resin as a main component (second polyester resin layer), and the polyester resin layer, the polyamide resin layer, and the second polyester resin layer can be stacked in sequence. The polyester resin layer and the second polyester resin layer may be the same or different.
[0057] First, the layer containing polyester resin as a main component (polyester resin layer) will be described.
[0058] The polyester resin layer is a layer containing polyester resin as the main component. Here, the main component refers to the component with the largest content among the components contained in the polyester resin layer, and preferably 80% by mass or more is polyester resin, more preferably 90% by mass or more is polyester resin, further preferably 95% by mass or more is polyester resin, and even more preferably 98% by mass or more is polyester resin.
[0059] The intrinsic viscosity of the polyester resin is preferably 0.50 to 0.90 dL / g.
[0060] The polyester resin may contain only one kind or two or more kinds. When containing two or more kinds, it is preferable that the total amount is within the above range.
[0061] In addition, various physical property values of polyester resins when two or more polyester resins are included are physical property values of the mixture unless otherwise specified. The mixture in this case refers to a mixture after melt kneading.
[0062] A first embodiment of the polyester resin contained in the polyester resin layer is a polyester resin having a melting point.
[0063] The melting point of the polyester resin in the first embodiment of the polyester resin is preferably 100 to 300° C., more preferably 200 to 300° C., and further preferably 220 to 295° C. The melting point is measured by the method described in Examples below. The same applies to the melting points shown below.
[0064] The glass transition temperature of the polyester resin of the first embodiment is preferably lower than 90°C, more preferably lower than 85°C, and further preferably lower than 80°C. In addition, the lower limit of the glass transition temperature is preferably higher than 60°C, more preferably higher than 65°C, and further preferably higher than 70°C. By using such a polyester resin, there is a tendency that the molding processability of the container is more excellent. The glass transition temperature is measured according to the method described in the examples described later. The same applies to the glass transition temperature described below.
[0065] As such a polyester resin, a polyester resin is one that is composed of a structural unit derived from a dicarboxylic acid and a structural unit derived from a diol, wherein 70 mol% or more (preferably 80 mol% or more, more preferably 90 mol% or more, and further preferably 95 mol% or more) of the structural unit derived from the dicarboxylic acid is derived from at least one selected from terephthalic acid and its esters, and 70 mol% or more (preferably 80 mol% or more, more preferably 90 mol% or more, and further preferably 95 mol% or more) of the structural unit derived from the diol is derived from ethylene glycol. Here, the polyester resin in the first embodiment is composed of a structural unit derived from a dicarboxylic acid and a structural unit derived from a diol, but may also contain structural units other than the structural unit derived from the dicarboxylic acid and the structural unit derived from the diol, and other parts such as terminal groups. The polyester resin used in the present invention is usually composed of a structural unit derived from a dicarboxylic acid and a structural unit derived from a diol, preferably 98 mol% or more. The same is true for other polyester resins below.
[0066] As the polyester resin that can be used in the first embodiment, the description in paragraphs 0064 to 0080 of JP-A-2016-169027 can be referred to, and the contents are incorporated into the present specification.
[0067] The second embodiment of the polyester resin contained in the polyester resin layer is an amorphous polyester resin. By using an amorphous polyester resin, a multi-layer container with better transparency can be obtained.
[0068] The glass transition temperature of the amorphous polyester resin is preferably 90° C. or higher, more preferably 100° C. or higher. The upper limit of the glass transition temperature is preferably 155° C. or lower, more preferably 150° C. or lower. By using such a polyester resin, a multilayer container having better heat resistance can be obtained.
[0069] As an example of the amorphous polyester resin, there can be mentioned a polyester resin composed of a structural unit derived from a dicarboxylic acid and a structural unit derived from a diol, wherein 70 mol% or more (preferably 80 mol% or more, more preferably 90 mol% or more, and further preferably 95 mol% or more) of the structural unit derived from the dicarboxylic acid are derived from at least one selected from terephthalic acid, naphthalene dicarboxylic acid and esters thereof, and 5 to 60 mol% (preferably 15 to 60 mol%) of the structural unit derived from the diol are derived from spiroglycol, and 95 to 40 mol% (preferably 85 to 40 mol%) are derived from ethylene glycol.
[0070] As another example of the amorphous polyester resin, there can be mentioned a polyester resin composed of a structural unit derived from a dicarboxylic acid and a structural unit derived from a diol, wherein 80 mol% or more (preferably 85 mol% or more, more preferably 90 mol% or more, and further preferably 95 mol% or more) of the structural unit derived from the dicarboxylic acid are derived from at least one selected from terephthalic acid, naphthalene dicarboxylic acid, and esters thereof, and 90 to 10 mol% (preferably 85 to 40 mol%) of the structural unit derived from the diol are derived from 1,4-cyclohexanedimethanol, and 10 to 90 mol% (preferably 15 to 60 mol%) are derived from ethylene glycol.
[0071] As the polyester resin used in the second embodiment, the polyester resin described in paragraphs 0010 to 0021 of Japanese Patent Application Publication No. 2006-111718, the polyester resin described in Japanese Patent Application Publication No. 2017-105873, and the polyester resin described in International Publication No. 2013 / 168804 can be referred to, and these contents are incorporated into this specification.
[0072] The polyester resin layer of the present invention may contain other components other than the polyester resin within the scope of the present invention. Specifically, various additives such as antioxidants, light stabilizers, ultraviolet absorbers, plasticizers, extenders, matting agents, drying regulators, antistatic agents, anti-settling agents, surfactants, flow improvers, drying oils, waxes, colorants, reinforcing agents, surface smoothing agents, leveling agents, curing reaction accelerators, and thickeners may be added. As other components, the description of paragraph 0026 of Japanese Patent Application Laid-Open No. 2006-111718 may be referred to, and these contents are incorporated into this specification.
[0073] Next, the layer containing polyamide resin as a main component (polyamide resin layer) will be described.
[0074] The polyamide resin layer is a layer having polyamide resin as the main component. The main component here refers to the component with the largest content among the components contained in the polyamide resin layer, preferably 80% by mass or more of the polyamide resin, more preferably 90% by mass or more of the polyamide resin, further preferably 95% by mass or more of the polyamide resin, and also preferably 98% by mass or more of the polyamide resin.
[0075] In addition, the polyamide resin layer preferably does not substantially contain polyester resin (further thermoplastic resin other than polyamide resin). Substantially free means that the content of polyester resin (further thermoplastic resin other than polyamide resin) is less than 2% by mass of the polyamide resin layer, preferably less than 1% by mass, more preferably less than 0.1% by mass, and may also be 0% by mass.
[0076] The polyamide resin may contain only one kind or two or more kinds. When containing two or more kinds, it is preferable that the total amount is within the above range.
[0077] The glass transition temperature of the polyamide resin is preferably 80°C or more, more preferably 85°C or more, and further preferably 90°C or more. By setting it to be above the aforementioned lower limit, an appropriate storage modulus G' can be formed during biaxial stretch blow molding within the temperature range during blow molding, and interlayer delamination of the container can be more effectively suppressed. In addition, the glass transition temperature of the polyamide resin is preferably 115°C or less, more preferably 110°C or less, further preferably 105°C or less, and may be 101°C or less. By setting it to be below the aforementioned upper limit, the effect of excellent moldability in a multilayer form with a polyester resin can be more effectively exerted.
[0078] When the polyamide resin contained in the polyamide resin layer is more than two kinds, the glass transition temperature of the polyamide resin is set to the glass transition temperature observed when measured in the state of the mixture. Wherein, when more than two glass transition points are observed, the highest glass transition temperature among them is used as the glass transition temperature in the resin composition. The mixture in this case refers to the mixture after melt kneading.
[0079] In the present invention, the polyamide resin includes the following xylylenediamine-based polyamide resin: composed of structural units derived from diamine and structural units derived from dicarboxylic acid, 70 mol% or more of the structural units derived from diamine are derived from meta-xylylenediamine, 80 to 97 mol% of the structural units derived from dicarboxylic acid are derived from α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 8 carbon atoms, and 20 to 3 mol% are derived from aromatic dicarboxylic acid (wherein the total of the structural units derived from α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 8 carbon atoms and the structural units derived from aromatic dicarboxylic acid does not exceed 100 mol%).
[0080] More preferably, 75 mol % or more, further preferably 80 mol % or more, still more preferably 90 mol % or more, and still more preferably 95 mol % or more of the structural units derived from diamine in the xylylenediamine-based polyamide resin are derived from meta-xylylenediamine.
[0081] Examples of the raw material diamine component other than meta-xylylenediamine include p-xylylenediamine, tetramethylenediamine, pentamethylenediamine, 2-methylpentanediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, dodecamethylenediamine, 2,2,4-trimethyl-hexamethylenediamine, and aliphatic diamines such as 2,4,4-trimethylhexamethylenediamine, 1,3-bis(aminomethyl)cyclohexane, Alicyclic diamines such as 1,4-bis(aminomethyl)cyclohexane, 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, bis(4-aminocyclohexyl)methane, 2,2-bis(4-aminocyclohexyl)propane, bis(aminomethyl)decalin, and bis(aminomethyl)tricyclodecane, and diamines having an aromatic ring such as bis(4-aminophenyl)ether, p-phenylenediamine, and bis(aminomethyl)naphthalene can be used alone or in combination of two or more.
[0082] The raw material dicarboxylic acid component of the xylylenediamine polyamide resin is 80 to 97 mol% derived from an α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 8 carbon atoms, and 20 to 3 mol% derived from an aromatic dicarboxylic acid. However, the total amount of the structural unit derived from the α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 8 carbon atoms and the structural unit derived from the aromatic dicarboxylic acid does not exceed 100 mol%.
[0083] Examples of the α,ω-straight chain aliphatic dicarboxylic acid having 4 to 8 carbon atoms include succinic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, and adipic acid, which can be used alone or in combination of two or more. Adipic acid is preferred as the α,ω-straight chain aliphatic dicarboxylic acid having 4 to 8 carbon atoms.
[0084] Examples of the aromatic dicarboxylic acid include phthalic acid compounds such as isophthalic acid, terephthalic acid, and phthalic acid, and isomers of naphthalene dicarboxylic acids such as 1,2-naphthalene dicarboxylic acid, 1,3-naphthalene dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, 2,5-furan dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 1,6-naphthalene dicarboxylic acid, 1,7-naphthalene dicarboxylic acid, 1,8-naphthalene dicarboxylic acid, 2,3-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, and 2,7-naphthalene dicarboxylic acid. One or more of them may be used. As the aromatic dicarboxylic acid, isophthalic acid is preferred.
[0085] Examples of the raw material dicarboxylic acid component other than the α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 8 carbon atoms and the aromatic dicarboxylic acid include aliphatic dicarboxylic acids having 9 or more carbon atoms and alicyclic dicarboxylic acids, and a mixture thereof may be used.
[0086] Examples of the aliphatic dicarboxylic acid having 9 or more carbon atoms include sebacic acid, undecanedioic acid, and dodecanedioic acid.
[0087] Examples of the alicyclic dicarboxylic acid include 1,3-cyclohexanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid.
[0088] It should be noted that the xylylenediamine-based polyamide resin is composed of structural units derived from diamines and structural units derived from dicarboxylic acids as described above, but structural units other than these are not completely excluded, and of course, structural units derived from lactams such as ε-caprolactam and laurolactam, and structural units derived from aliphatic aminocarboxylic acids such as aminocaproic acid and aminoundecanoic acid may also be included. In the present invention, the total of structural units derived from diamines and structural units derived from dicarboxylic acids in the xylylenediamine-based polyamide resin preferably accounts for 90% or more of all structural units, more preferably 95% or more, and even more preferably 99% or more of all structural units excluding terminal groups.
[0089] The polyamide resin contained in the polyamide resin layer may be composed of only the above-mentioned xylylenediamine-based polyamide resin, or may contain other polyamide resins. Details of other polyamide resins will be described later.
[0090] The xylylenediamine polyamide resin may be a crystalline polyamide resin or an amorphous polyamide resin, but is usually a crystalline polyamide resin. In the present invention, when a crystalline polyamide resin is used in the polyamide resin layer, oriented crystallization occurs due to biaxial stretching blow molding, and barrier properties are improved. In addition, creep of the bottle can be suppressed.
[0091] Here, the amorphous polyamide resin refers to a polyamide resin having a crystal melting enthalpy ΔHm of 5 J / g or less. The crystal melting enthalpy (ΔHm) is measured according to the method described in the examples described below.
[0092] On the other hand, when the polyamide resin layer of the present invention contains two or more polyamide resins, it is preferred that at least one of the polyamide resins contained is an amorphous resin. When an amorphous polyamide resin is used in the polyamide resin layer, the storage modulus G' of the polyamide resin tends to increase, and interlayer delamination of the container can be more effectively suppressed.
[0093] One embodiment of the polyamide resin of the present invention is a mixture of a crystalline polyamide resin and an amorphous polyamide resin. When the mixture is used, a polyamide resin having both the advantages of the crystalline polyamide resin and the advantages of the amorphous polyamide resin can be obtained.
[0094] When a mixture of a crystalline polyamide resin and an amorphous polyamide resin is used, the mixing ratio is preferably 60 to 95 parts by mass of the crystalline polyamide resin and 40 to 5 parts by mass of the amorphous polyamide resin, more preferably 70 to 95 parts by mass of the crystalline polyamide resin and 30 to 5 parts by mass of the amorphous polyamide resin, further preferably 80 to 95 parts by mass of the crystalline polyamide resin and 20 to 5 parts by mass of the amorphous polyamide resin, and still more preferably 85 to 95 parts by mass of the crystalline polyamide resin and 15 to 5 parts by mass of the amorphous polyamide resin.
[0095] When a mixture of a crystalline polyamide resin and an amorphous polyamide resin is used, a mixture of a crystalline xylylenediamine-based polyamide resin and an amorphous polyamide resin is preferred.
[0096] The polyamide resin contained in the polyamide resin layer is particularly preferably also composed of an amorphous polyamide resin (excluding those belonging to the aforementioned xylylenediamine-based polyamide resin), and the ratio of the xylylenediamine-based polyamide resin to the amorphous polyamide resin (excluding those belonging to the xylylenediamine-based polyamide resin) is as follows: 40 to 5 parts by mass of the amorphous polyamide resin relative to 60 to 95 parts by mass of the xylylenediamine-based polyamide resin.
[0097] The preferred range of the mixing ratio of the xylylenediamine polyamide resin and the amorphous polyamide resin (excluding those belonging to the xylylenediamine polyamide resin) is more preferably 70 to 95 parts by mass of the xylylenediamine polyamide resin and 30 to 5 parts by mass of the amorphous polyamide resin (excluding those belonging to the xylylenediamine polyamide resin), further preferably 80 to 95 parts by mass of the xylylenediamine polyamide resin and 20 to 5 parts by mass of the amorphous polyamide resin (excluding those belonging to the xylylenediamine polyamide resin), and still more preferably 85 to 95 parts by mass of the xylylenediamine polyamide resin and 15 to 5 parts by mass of the amorphous polyamide resin (excluding those belonging to the xylylenediamine polyamide resin).
[0098] Here, preferred embodiments of the amorphous polyamide resin will be described.
[0099] An example of an embodiment of the amorphous polyamide resin is a polyamide resin (hereinafter sometimes referred to as "first amorphous polyamide resin") consisting of a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, wherein 70 mol% or more of the diamine-derived structural unit is derived from xylylenediamine, and 30 to 65 mol% of the dicarboxylic acid-derived structural unit is derived from α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 8 carbon atoms, and 70 to 35 mol% is derived from isophthalic acid (wherein the total does not exceed 100 mol%). By blending such a first amorphous polyamide resin, the transparency and oxygen barrier properties of the container can be further improved.
[0100] More preferably, 75 mol% or more, further preferably 80 mol% or more, still preferably 90 mol% or more, and even more preferably 95 mol% or more of the structural units derived from diamine in the first amorphous polyamide resin are derived from xylylenediamine (preferably at least one of m-xylylenediamine and p-xylylenediamine). The xylylenediamine preferably contains at least m-xylylenediamine, more preferably 20 mol% or more of the xylylenediamine is m-xylylenediamine, further preferably 50 mol% or more of the xylylenediamine is m-xylylenediamine, further preferably 70 mol% or more of the xylylenediamine is m-xylylenediamine, and even more preferably 90 mol% or more of the xylylenediamine is m-xylylenediamine.
[0101] Examples of the raw material diamine component other than xylylenediamine include raw material diamine components other than xylylenediamine among the raw material diamines of the above-mentioned xylylenediamine-based polyamide resins.
[0102] The dicarboxylic acid-derived structural unit in the first amorphous polyamide resin is as described above, and 30 to 65 mol % is derived from a C4-8 α,ω-linear aliphatic dicarboxylic acid (preferably adipic acid), and 70 to 35 mol % is derived from isophthalic acid.
[0103] The lower limit of the ratio of isophthalic acid in all dicarboxylic acids constituting the structural unit derived from dicarboxylic acid in the first amorphous polyamide resin is 35 mol% or more, preferably 40 mol% or more, and more preferably 41 mol% or more. The upper limit of the ratio of isophthalic acid is 70 mol% or less, preferably 67 mol% or less, more preferably 65 mol% or less, further preferably 62 mol% or less, still preferably 60 mol% or less, and may be 58 mol% or less. By setting it in such a range, there is a tendency that the oxygen barrier property of the obtained multilayer container is further improved.
[0104] The lower limit of the proportion of α,ω-straight-chain aliphatic dicarboxylic acid (preferably adipic acid) having 4 to 8 carbon atoms in all dicarboxylic acids constituting the structural unit derived from dicarboxylic acid in the first amorphous polyamide resin is 30 mol% or more, preferably 33 mol% or more, more preferably 35 mol% or more, further preferably 38 mol% or more, still preferably 40 mol% or more, and may be 42 mol% or more. The upper limit of the proportion of the aforementioned α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 8 carbon atoms is 65 mol% or less, preferably 60 mol% or less, and more preferably 59 mol% or less. By setting it in this range, there is a tendency that the oxygen barrier properties of the multilayer container in the present invention are further improved.
[0105] The ratio of the total amount of isophthalic acid and α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 8 carbon atoms in all dicarboxylic acids constituting the structural unit derived from dicarboxylic acid in the first amorphous polyamide resin is preferably 90 mol% or more, more preferably 95 mol% or more, further preferably 98 mol% or more, and may be 100 mol%. By setting such a ratio, the transparency of the multi-layer container in the present invention tends to be further improved.
[0106] Examples of the dicarboxylic acid component other than the α,ω-linear aliphatic dicarboxylic acid having 4 to 8 carbon atoms and isophthalic acid in the first amorphous polyamide resin include the components other than the α,ω-linear aliphatic dicarboxylic acid having 4 to 8 carbon atoms and isophthalic acid mentioned above as the raw material dicarboxylic acid component of the xylylenediamine-based polyamide resin.
[0107] The first amorphous polyamide resin preferably does not substantially contain a structural unit derived from terephthalic acid. Substantially free means that the molar amount of isophthalic acid contained in the first amorphous polyamide resin is 5 mol% or less, preferably 3 mol% or less, and more preferably 1 mol% or less. By setting such a configuration, the appropriate molding processability of the container is maintained, and the gas barrier property becomes less likely to change due to humidity.
[0108] Another example of the embodiment of the amorphous polyamide resin is a polyamide resin (hereinafter sometimes referred to as "second amorphous polyamide resin") composed of a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, wherein 70 mol% or more of the diamine-derived structural unit is derived from hexamethylenediamine, 55 mol% or more of the dicarboxylic acid-derived structural unit is derived from isophthalic acid, and 15 mol% or more of the dicarboxylic acid-derived structural unit is derived from terephthalic acid (wherein the total of isophthalic acid and terephthalic acid does not exceed 100 mol%). By blending the second amorphous polyamide resin, the interlayer delamination resistance of the obtained multilayer container can be further improved.
[0109] In the second amorphous polyamide resin, preferably 80 mol% or more, more preferably 90 mol% or more, further preferably 95 mol% or more, and still more preferably 99 mol% or more of the structural units derived from diamine are derived from hexamethylenediamine. As diamines other than hexamethylenediamine that can be used as the raw material diamine component of the second amorphous polyamide resin, components other than hexamethylenediamine described as the raw material diamine component of the first embodiment of the above-mentioned xylylenediamine-based polyamide resin can be exemplified.
[0110] In the second amorphous polyamide resin, 55 mol% or more of the structural units derived from dicarboxylic acid are derived from isophthalic acid, and the proportion is preferably 60 mol% or more. The structural units derived from isophthalic acid are preferably 85 mol% or less, more preferably 80 mol% or less, and further preferably 75 mol% or less.
[0111] In addition, in the second amorphous polyamide resin, more than 15 mol% of the structural units derived from dicarboxylic acid are derived from terephthalic acid, and the proportion is preferably more than 20 mol%, and more preferably more than 25 mol%. The structural units derived from terephthalic acid are more preferably less than 45 mol%, and more preferably less than 40 mol%. In the second amorphous polyamide resin, preferably more than 80 mol%, more preferably more than 90 mol%, more preferably more than 95 mol%, and more preferably more than 99 mol% of the structural units derived from dicarboxylic acid are composed of isophthalic acid and terephthalic acid. As dicarboxylic acids other than isophthalic acid and terephthalic acid, which are preferably used as the raw material dicarboxylic acid components of the second amorphous polyamide resin, examples thereof include substances other than dicarboxylic acids of isophthalic acid and terephthalic acid described as the raw material dicarboxylic acid components of the first embodiment of the above-mentioned xylene diamine-based polyamide resin.
[0112] In addition, the polyamide resin layer used in the present invention may contain other polyamide resins other than those mentioned above within the scope of the present invention. Specifically, polyamide 6, 11, 12, 46, 66, 610, 612, 6I, 6 / 66, 6 / 6T, 66 / 6T, polytrimethylhexamethylene terephthalamide, polybis(4-aminocyclohexyl)methane dodecylamide, polybis(3-methyl-4-aminocyclohexyl)methane dodecylamide, polyundemethylene hexahydroterephthalamide, and the polyamide resins of the phenylenediamine series described in detail below may be cited. It should be noted that the above-mentioned "I" represents an isophthalic acid component, and "T" represents a terephthalic acid component. In addition, as the polyamide resin that can be used in the present invention, reference can be made to the description of paragraphs 0011 to 0013 of JP-A-2011-132550, the polyamide resin described in International Publication No. 2012 / 014772, the polyamide resin described in International Publication No. 2016 / 208272, the polyamide resin described in International Publication No. 2017 / 134946, the polyamide resin described in International Publication No. 2017 / 090556, the polyamide resin described in International Publication No. 2018 / 074234, and the polyamide resin described in International Publication No. 2018 / 155171, and these contents are incorporated into this specification.
[0113] When the multilayer container of the present invention is required to have barrier properties, the polyamide resin contained in the polyamide resin layer is preferably a polyamide resin having barrier properties. For example, a polyamide resin having a low oxygen permeability value is preferred. Specifically, an oxygen permeability coefficient of 5.0 cc·mm / (m 2 ·day·atm) or less (more preferably 1.0cc·mm / (m 2·day·atm) or less) of polyamide resin.
[0114] The number average molecular weight of the polyamide resin used in the present invention is preferably 5000 to 200000, more preferably 10000 to 50000. The number average molecular weight is measured according to the description in paragraph 0057 of International Publication No. 2019 / 026499.
[0115] In addition, the polyamide resin layer in the present invention may include, within the scope that does not impair the purpose of the present invention: inorganic fillers such as glass fiber and carbon fiber; plate-shaped inorganic fillers such as glass flakes, talc, kaolin, mica, montmorillonite, and organized clay; impact-resistant modifiers such as various elastomers; crystal nucleating agents; lubricants such as fatty amides, fatty amide compounds, and higher fatty acid metal salts (such as calcium stearate); antioxidants such as copper compounds, organic or inorganic halogen compounds, hindered phenols, hindered amines, hydrazines, sulfur compounds, and phosphorus compounds; anti-coloring agents; spreading agents; ultraviolet absorbers such as benzotriazoles; additives such as release agents, plasticizers, colorants, and flame retardants; oxidation reaction accelerators, compounds containing benzoquinones, anthraquinones, and naphthoquinones, and other additives.
[0116] Next, the layer structure of the preform and the multi-layer container obtained from the preform will be described.
[0117] The preform and multilayer container used in the present invention are multilayer containers having at least one layer mainly composed of polyester resin (polyester resin layer) and one layer mainly composed of polyamide resin (polyamide resin layer). The polyester resin layer and the polyamide resin layer are usually in contact.
[0118] The number of layers constituting the multilayer container is preferably at least 3. In the present invention, a form including at least 2 polyester resin layers and at least 1 polyamide resin layer can be exemplified. In this case, it is preferred that the polyester resin layer, the polyamide resin layer, and the polyester resin layer are stacked in this order.
[0119] More specifically, the number of layers constituting the multilayer container is more preferably 3 to 10 layers, and further preferably 3 to 5 layers.
[0120] The number of polyester resin layers in the multilayer container is preferably 1 to 5, more preferably 2 to 4. The number of polyamide resin layers in the multilayer container is preferably 1 to 3, more preferably 1 or 2.
[0121] For example, the multi-layer container can be a polyester resin layer / polyamide resin layer structure (the polyester resin layer is the inner layer) comprising one polyester resin layer and one polyamide resin layer, or a polyamide resin layer / polyester resin layer structure (the polyamide resin layer is the inner layer), or a three-layer structure of polyester resin layer / polyamide resin layer / polyester resin layer comprising two polyester resin layers and one polyamide resin layer, or a five-layer structure of polyester resin layer / polyamide resin layer / polyester resin layer / polyamide resin layer / polyester resin layer.
[0122] From the viewpoint of better interlayer peeling resistance, the polyamide resin layer is preferably centrally arranged or internally arranged, more preferably internally arranged. "The polyamide resin layer is centrally arranged" means that, in a cross section in the thickness direction of the multilayer container, the polyamide resin layer is present near the center in the thickness direction. "The polyamide resin layer is internally arranged" means that, in a cross section in the thickness direction of the multilayer container, the polyamide resin layer is present at a position close to the inner surface side in the thickness direction. As the position of the polyamide resin layer of the present invention, for example, the method in which the intermediate layer in Japanese Patent Publication No. 02-229023 is a polyamide resin layer can be exemplified, and the contents of the same publication are introduced into this specification.
[0123] The multi-layer container in the present invention may include any layer in addition to the aforementioned polyester resin layer and polyamide resin layer depending on desired performance and the like.
[0124] [Multi-layer container]
[0125] The shape of the multilayer container in the present invention is not particularly limited, and examples thereof include molded containers such as bottles and cups, with bottles being preferred.
[0126] In addition, the polyester resin layer and the polyamide resin layer do not need to be included in the entire part of the bottle. For example, a mode in which the polyamide resin layer is included in the main body of the bottle and the polyamide resin layer is not included near the opening (plugging part) can be exemplified. However, when the polyamide resin layer is present even near the opening of the bottle, the barrier performance is further improved, which is preferred.
[0127] The oxygen permeability of the multilayer container (preferably a bottle) of the present invention is preferably 0.02cc / (bottle·day·0.21atm) or less. The lower limit is not particularly limited, but is practically 0.0001cc / (bottle·day·0.21atm) or more. The oxygen permeability is measured by the method described in the Examples described below.
[0128] The capacity of the multi-layer container in the present invention is preferably 0.1 to 2.0 L, more preferably 0.2 to 1.5 L, and even more preferably 0.3 to 1.0 L, in view of the storage stability of the contents.
[0129] The thickness of the inner layer (eg polyester resin layer) of the multilayer container of the present invention is preferably 0.01 mm or more, more preferably 0.03 mm or more, further preferably 0.05 mm or more, and is preferably 2.0 mm or less, more preferably 1.5 mm or less, further preferably 1.0 mm or less.
[0130] The thickness of the outer layer (eg polyester resin layer) is preferably 0.01 mm or more, more preferably 0.05 mm or more, and is preferably 2.0 mm or less, more preferably 1.5 mm or less, and further preferably 1.0 mm or less.
[0131] In addition, the thickness of the polyamide resin layer is preferably 0.005 mm or more, more preferably 0.01 mm or more, and further preferably 0.02 mm or more, and preferably 0.2 mm or less, more preferably 0.15 mm or less, and further preferably 0.1 mm or less. In the case of having two or more polyamide resin layers, the total thickness of the polyamide resin layers is preferably the above thickness.
[0132] In addition, when there are two or more polyamide resin layers and an intermediate layer between the polyamide resin layers, the thickness of the intermediate layer is preferably greater than 0.01 mm, more preferably greater than 0.03 mm, and further preferably greater than 0.05 mm, and is preferably less than 2.0 mm, more preferably less than 1.5 mm, and further preferably less than 1.0 mm.
[0133] In the multilayer container (especially bottle) of the present invention, the mass of the polyamide resin layer is preferably 1 to 20 mass %, more preferably 2 to 15 mass %, and particularly preferably 3 to 10 mass % relative to the total mass of the multilayer container. By setting the mass of the polyamide resin layer to the above range, a multilayer container with good gas barrier properties can be obtained.
[0134] The objects stored in the multilayer container of the present invention are not particularly limited, and examples thereof include food, cosmetics, medicines, toiletry tools, mechanical / electrical / electronic parts, oils, resins, etc., but the multilayer container of the present invention can be particularly suitably used as a container for storing food.
[0135] Examples of food include processed seafood, processed livestock, rice, and liquid food. They are particularly suitable for preserving foods that are susceptible to the effects of oxygen. For their details, reference can be made to paragraphs 0032 to 0035 of Japanese Patent Gazette No. 2011-037199, and these contents are incorporated into this specification. If specific examples of food are shown, for example, beverages such as vegetable juice, fruit juice, tea, coffee / coffee beverages, milk / milk beverages, mineral water, ionic beverages, alcoholic beverages, lactic acid bacteria beverages, and soy milk can be cited; gel-like foods such as tofu, egg tofu, jelly, pudding, water jelly, mousse, yogurt, and almond tofu; sauces, soy sauce, ketchup, noodle soup, dressing, vinegar, liqueur, seasonings, jam, mayonnaise, miso, kimchi juice, and ground spices; salami, ham, sausage, grilled chicken skewers, meatballs, hamburgers, roast pork, Processed meat products such as beef jerky; processed seafood products such as fish cakes, boiled shellfish, boiled fish, and chikuwa; processed rice products such as porridge, cooked rice, mixed rice, and red bean rice; sauces such as meat sauce, mapo tofu sauce, spaghetti sauce, curry sauce, stew sauce, and diced meat sauce; processed dairy products such as cheese, butter, cream, and condensed milk; processed egg products such as boiled eggs and hot spring eggs; boiled vegetables / beans; side dishes such as fried, steamed, stir-fried, boiled, and grilled food; kimchi; noodles / spaghetti such as udon, soba, and spaghetti; pickled fruit juice, etc.
[0136] Depending on the storage object, the multi-layer container can be sterilized or disinfected using ultraviolet rays, electron beams, gamma rays, X-rays, etc.
[0137] Example
[0138] The present invention is further specifically described by enumerating examples below. The materials, dosage, ratio, processing content, processing steps, etc. shown in the following examples can be appropriately changed as long as they do not depart from the gist of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below.
[0139] [raw materials]
[0140] MXD6I (isophthalic acid (PIA) 6 mol%):
[0141] Polyamide resin synthesized from m-xylylenediamine and dicarboxylic acid (94 mol% of adipic acid and 6 mol% of isophthalic acid), MX Nylon K7007C, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight: 22,000, crystalline resin
[0142] MXD6I (PIA 15 mol%):
[0143] The polyamide resin and crystalline resin synthesized according to the synthesis example described below
[0144] MXD6I (PIA 50 mol%):
[0145] The polyamide resin and the amorphous resin synthesized according to the synthesis example described below
[0146] 6I / 6T:
[0147] Polyamide resin synthesized from hexamethylenediamine, isophthalic acid and terephthalic acid, G21, manufactured by EMS, number average molecular weight: 15,000, amorphous resin
[0148] PA6:
[0149] Made by Ube Kosan Co., Ltd., UBE Nylon 1022B, number average molecular weight: 22000
[0150] MXD10:
[0151] Polyamide resin synthesized from m-xylylenediamine and sebacic acid, LEXTER 8000, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight: 15,000, crystalline resin
[0152] MXD6:
[0153] Polyamide resin synthesized from m-xylylenediamine and adipic acid, MX Nylon S6007, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight: 22,000, crystalline resin
[0154] <Synthesis of MXD6I (PIA 15 mol%)>
[0155] In a reaction vessel equipped with a stirrer, a partial condenser, a full condenser, a thermometer, a dropping funnel, a nitrogen inlet tube, and a strand die, accurately weighed adipic acid 10201 g (69.80 mol), isophthalic acid 2047 g (12.32 mol), calcium hypophosphite (Ca(H 2 PO 2 ) 2 ) 1.73g (the phosphorus atom concentration in the polyamide resin is 30 mass ppm), 1.11g of sodium acetate, after sufficient nitrogen replacement, nitrogen was filled until the internal pressure reached 0.4MPa, and then the system was heated to 190°C while stirring under a small amount of nitrogen flow. The molar ratio of sodium acetate / calcium hypophosphite was set to 1.33.
[0156] 11185 g (82.12 mol) of meta-xylylenediamine was added dropwise thereto under stirring, and the generated condensation water was removed to the outside of the system while the temperature in the system was continuously raised. After the addition of meta-xylylenediamine was completed, the internal temperature was raised, and the pressure in the reaction vessel was reduced when it reached 265°C, and the internal temperature was further raised, and the melt polycondensation reaction was continued at 270°C for 10 minutes. After that, the system was pressurized with nitrogen, and the obtained polymer was taken out from the strand die, and pelletized to obtain about 20 kg of polyamide resin pellets (MXD6I (PIA 15 mol%)). The obtained polyamide resin (MXD6I (PIA 15 mol%)) was vacuum dried at 90°C for 24 hours.
[0157] The number average molecular weight of the obtained polyamide resin (MXD6I (PIA 15 mol %)) was 13,000.
[0158] <Synthesis of MXD6I (PIA 50 mol%)>
[0159] In a reaction vessel equipped with a stirrer, a partial condenser, a full condenser, a thermometer, a dropping funnel, a nitrogen inlet tube, and a strand die, 6001 g (41.06 mol) of adipic acid, 6822 g (41.06 mol) of isophthalic acid, and sodium hypophosphite monohydrate (NaH 2 PO 2 ) 7.23g (the phosphorus atom concentration in the polyamide resin is 100 mass ppm), sodium acetate 7.44g, after sufficient nitrogen replacement, nitrogen was filled until the internal pressure reached 0.4MPa, and then the system was heated to 190°C while stirring under a small amount of nitrogen flow. The molar ratio of sodium acetate / sodium hypophosphite monohydrate was set to 1.33.
[0160] 11185 g (82.12 mol) of meta-xylylenediamine was added dropwise thereto under stirring, and the system was continuously heated while the generated condensation water was removed to the outside of the system. After the addition of meta-xylylenediamine was completed, the internal temperature was raised, and the pressure in the reaction vessel was reduced when it reached 265°C, and the internal temperature was further raised, and the melt polycondensation reaction was continued at 270°C for 10 minutes. After that, the system was pressurized with nitrogen, and the obtained polymer was taken out from the strand die, and pelletized to obtain about 20 kg of polyamide resin pellets (MXD6I (PIA 50 mol%)). The obtained polyamide resin (MXD6I (PIA 50 mol%)) was vacuum dried at 90°C for 24 hours.
[0161] The crystal melting enthalpy ΔHm of the obtained polyamide resin (MXD6I (PIA 50 mol%)) during the heating process was approximately 0 J / g, indicating that the polyamide resin was amorphous. The number average molecular weight was 13,000.
[0162] <Glass transition temperature, melting point and crystal melting enthalpy>
[0163] The differential scanning calorimetry was performed in accordance with JIS K7121 and K7122. Using a differential scanning calorimeter, the resin pellets were crushed and placed in a measuring dish of the differential scanning calorimeter, and the temperature was raised to 300°C at a heating rate of 10°C / min in a nitrogen atmosphere, and the temperature was measured after a pre-treatment of rapid cooling. The measurement conditions were as follows: after maintaining at 300°C for 5 minutes at a heating rate of 10°C / min, the temperature was lowered to 100°C at a cooling rate of -5°C / min, and the glass transition temperature (Tg), melting point (Tm) and crystal melting enthalpy (ΔHm) were determined.
[0164] As a differential scanning calorimeter, "DSC-60" manufactured by SHIMADZU CORPORATION was used.
[0165] In addition, when using a mixture of two or more types as a resin, the above-mentioned each characteristic value is set as the value for the resin after melt-kneading.
[0166] <Measurement of storage modulus G'>
[0167] The storage modulus G' of the polyamide resin is measured by the following method.
[0168] In order to form the composition of the polyamide resin layer shown in Table 1, when one polyamide resin is used, the pellets are used directly. For the method of using two or more polyamide resins, the pellets are dry-mixed and supplied to a single-screw extruder with a T-die and kneaded. At an extrusion temperature of 260°C, melt extrusion is performed from the die to obtain a film with a width of 150 mm and a thickness of 500 μm. The obtained film is humidity-adjusted to make it the same as the moisture content of the preform recorded in Table 1, and then cut into strips with a width of 5 mm and a length of 40 mm. The sample is subjected to a dynamic viscoelasticity test under the following conditions using a dynamic viscoelasticity measuring device to measure the storage modulus G' at the temperature of the preform shown in Table 1. The temperature of the preform here refers to the temperature of the preform during biaxial stretch blow molding, specifically, the temperature measured by a non-contact thermometer at the stage where heating is completed through the preform heating zone of the blow molding machine.
[0169] Measurement mode: Stretch mode
[0170] Amplitude: 10μm
[0171] Frequency: 1Hz
[0172] Heating rate: 2℃ / min
[0173] It should be noted that, in this embodiment, the single screw extruder with a T-die is PTM-30 manufactured by Research Laboratory of Plastics Technology Co., Ltd., and the dynamic viscoelasticity measuring device is EXSTAR DMA6100 manufactured by SII. However, when the aforementioned extruder and / or device is difficult to obtain due to discontinuation of production, other extruders with equivalent performance may be used.
[0174] PET: A thermoplastic polyester resin synthesized from terephthalic acid and ethylene glycol, manufactured by Mitsubishi Chemical Corporation, Unipet BK2180, melting point 248°C, glass transition temperature 75°C, intrinsic viscosity = 0.83 dL / g. When used, the one dried in a dehumidifying dryer at 150°C for 8 hours was used. The intrinsic viscosity was measured as follows: the polyester resin was dissolved in a mixed solvent of phenol / 1,1,2,2-tetrachloroethane = 6 / 4 (mass ratio), maintained at 25°C, and measured using an Ubbelohde viscometer.
[0175] [Examples 1, 2, Comparative Examples 1 to 4]
[0176] <Manufacturing of preforms>
[0177] Using an injection molding machine with two injection barrels (manufactured by Sumitomo Heavy Industries, Ltd., model SE-DU130CI) and a multi-layer hot runner mold with two mold grooves (manufactured by Kortec), a portion of preforms having a three-layer structure including (Y) / (X) / (Y) were manufactured under the conditions shown below.
[0178] Specifically, first, a thermoplastic polyester resin (PET) constituting the material of layer (Y) is injected into the cavity of the mold from an injection barrel, and while maintaining the injected state of layer (Y), a polyamide resin of the composition of the polyamide resin layer shown in Table 1 as a material constituting layer (X) to be a polyamide resin layer is injected from another injection barrel together with the PET constituting layer (Y), and finally a necessary amount of PET constituting layer (Y) is injected to fill the cavity, thereby obtaining a preform (25 g) in which a part of the preform has a three-layer structure of (Y) / (X) / (Y). The shape of the preform is a preform with a total length of 92 mm, an outer diameter of 22 mm, and a wall thickness of 3.9 mm. The preform is immediately packaged in a moisture-proof packaging after being manufactured, and is stored in this state until the start of the biaxial stretch blow molding described later.
[0179] <<Molding conditions>>
[0180] Skin side (Y) injection barrel temperature: 285℃
[0181] Core side (X) injection barrel temperature: 265℃
[0182] Resin flow path temperature in mold: 290℃
[0183] Mold cooling water temperature: 15℃
[0184] Cycle time: 33 seconds
[0185] <Measurement of moisture content>
[0186] The moisture content of the preform was measured by the following method.
[0187] The preform after the moisture-proof packaging was taken out, and after separating the layer (X) and the layer (Y), the moisture content of the layer (X) was measured using a Karl Fischer moisture meter under a nitrogen atmosphere at 230° C. for 30 minutes.
[0188] The Karl Fischer moisture meter used was GT-200 manufactured by Mitsubishi Chemical Analytech Co., Ltd.
[0189] When the preform is not packaged to prevent moisture, the moisture content is recorded as the moisture content measured immediately before the start of biaxial stretch blow molding.
[0190] In addition, the unit of water content is mass %, and in this specification, it may be abbreviated and expressed as %.
[0191] <Manufacturing of multi-layer containers>
[0192] The preform was subjected to biaxial stretch blow molding using a biaxial stretch blow molding device (manufactured by Frontier, model EFB1000ET) to obtain a petal-shaped bottle (multilayer container). The bottle (multilayer container) had a total length of 223 mm, an outer diameter of 65 mm, and an internal volume of 500 mL (surface area: 0.04 m 2 , average thickness of the main body: 0.33 mm), the bottom is petal-shaped. No concave grooves are provided on the main body. The biaxial stretch blow molding conditions are as follows. The proportion of layer (X) is 5% by mass relative to the total mass of the obtained bottle (multilayer container).
[0193] Preform temperature: Temperature listed in Table 1 (°C)
[0194] One-time blowing pressure: 0.9MPa
[0195] Secondary blow molding pressure: 2.5MPa
[0196] One blow molding delay time: 0.30 seconds
[0197] Blowing time: 0.30 seconds
[0198] Second blow molding time: 2.0 seconds
[0199] Blow molding exhaust time: 0.6 seconds
[0200] Mold temperature: 30℃
[0201] <Interlayer delamination>
[0202] The obtained multilayer container was evaluated for interlayer peeling properties as follows.
[0203] First, the multilayer container obtained above was filled with 500 mL of colored carbonated water (4.2 gas volumes), and after the lid was closed, it was left to stand at 23°C for 7 days. After that, the side impact test was implemented by applying an impact to the side of the bottle (a position 123 mm above the bottom) using a pendulum with an impact load (2825 g). Since the interlayer peeling part will appear turbid and can be distinguished visually, the presence or absence of interlayer peeling of the multilayer container is visually determined. It should be noted that even if only a part of the multilayer container has undergone interlayer peeling, it is considered that interlayer peeling has occurred. The number of multilayer containers tested is set to 5, and the interlayer peeling property is evaluated based on the value obtained by averaging the number of impacts when interlayer peeling occurs.
[0204] The results are shown in Table 1.
[0205] <Oxygen Transmission Rate (OTR)>
[0206] With respect to the obtained multilayer container, the oxygen permeability was evaluated as follows.
[0207] Specifically, the multilayer container prepared in the examples and comparative examples was filled with 100 mL of water, and nitrogen gas of 1 atm was circulated at 20 mL / min in the multilayer container under the conditions of an oxygen partial pressure of 0.21 atm, an internal humidity of 100% RH (relative humidity), an external humidity of 50% RH, and a temperature of 23° C. After 200 hours, the amount of oxygen contained in the nitrogen gas that circulated in the multilayer container was detected by a coulometric sensor to measure the oxygen permeability. The unit is expressed as cc / (bottle·day·0.21 atm).
[0208] The oxygen permeability measuring device used was "OX-TRAN 2 / 61", manufactured by MOCON.
[0209] The results are shown in Table 1.
[0210] [Examples 3 and 4]
[0211] <Manufacturing of preforms>
[0212] Using an injection molding machine with two injection barrels (manufactured by Sumitomo Heavy Industries, Ltd., model SE-DU130CI) and a multi-layer hot runner mold with two mold grooves (manufactured by Kortec), a portion of preforms having a three-layer structure including (Y) / (X) / (Y) were manufactured under the conditions shown below.
[0213] Specifically, first, a thermoplastic polyester resin (PET) constituting the material of layer (Y) is injected from an injection barrel into the cavity of the mold, and while maintaining the injected state of layer (Y), a material constituting layer (X) to be a polyamide resin layer, which is a mixture of two kinds of mixed polyamide resin pellets in a manner to form the composition of the polyamide resin layer shown in Table 1, is injected from another injection barrel together with the PET constituting layer (Y), and finally a necessary amount of PET constituting layer (Y) is injected to fill the cavity, thereby obtaining a preform (25 g) in which a part of the preform has a three-layer structure of (Y) / (X) / (Y). The shape of the preform is a parison with a total length of 92 mm, an outer diameter of 22 mm, and a wall thickness of 3.9 mm. The preform is immediately packaged in a moisture-proof packaging after being manufactured, and is stored in this state until the start of the biaxial stretch blow molding described later.
[0214] <<Molding conditions>>
[0215] Skin side (Y) injection barrel temperature: 285℃
[0216] Core side (X) injection barrel temperature: 265℃
[0217] Resin flow path temperature in mold: 290℃
[0218] Mold cooling water temperature: 15℃
[0219] Cycle time: 33 seconds
[0220] The measurement of the moisture content, the production of a multilayer container, the evaluation of the interlayer delamination property, and the evaluation of the oxygen permeability (OTR) were carried out in the same manner as in Example 1. The results are shown in Table 1.
[0221] [Table 1]
[0222]
[0223] The above results show that the multilayer container obtained by the production method of the present invention has excellent interlayer delamination properties and also has low oxygen permeability (Examples 1 to 4).
[0224] In contrast, when the storage modulus G' is high (Comparative Examples 1 and 2), the interlayer delamination is poor. In addition, when the moisture content of the preform is high and the storage modulus G' is low (Comparative Example 3), the interlayer delamination is also poor. In addition, when the dicarboxylic acid constituting the polyamide resin does not contain an aromatic dicarboxylic acid (Comparative Examples 1 to 4), the interlayer delamination is poor regardless of the storage modulus G'.
[0225] Description of Reference Numerals
[0226] 1 Preform
[0227] 2 Heater
[0228] 3. Mould
[0229] 4 Tension rod
[0230] 5 Multi-layer container
Claims
1. A method for producing a multi-layer container, comprising the steps of: biaxially stretching and blow-molding a preform having a layer mainly composed of a polyester resin and a layer mainly composed of a polyamide resin, The storage modulus G' of the polyamide resin obtained by measuring the dynamic viscoelasticity of the preform at a temperature and a frequency of 1 Hz during the biaxial stretch blow molding is 5 to 30 MPa, The moisture content of the layer containing the polyamide resin as a main component in the preform immediately before the biaxial stretch blow molding is 0.5% or less, The polyamide resin comprises the following xylylenediamine-based polyamide resin: composed of a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, wherein 70 mol% or more of the diamine-derived structural unit is derived from meta-xylylenediamine, and 80 to 97 mol% of the dicarboxylic acid-derived structural unit is derived from an α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 8 carbon atoms, and 20 to 3 mol% is derived from an aromatic dicarboxylic acid, wherein: The total amount of the structural unit derived from the α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 8 carbon atoms and the structural unit derived from the aromatic dicarboxylic acid is not more than 100 mol%. The glass transition temperature of the polyamide resin is greater than 90°C.
2. The method for manufacturing a multi-layer container according to claim 1, wherein: The heating temperature of the preform during the biaxial stretch blow molding is equal to or higher than the glass transition temperature of the polyamide resin and equal to or lower than 115° C.
3. The method for manufacturing a multi-layer container according to claim 1 or 2, wherein: The storage modulus G' is 15 to 30 MPa.
4. The method for manufacturing a multi-layer container according to claim 1 or 2, wherein: The moisture content is 0.1-0.45%.
5. The method for manufacturing a multi-layer container according to claim 1 or 2, wherein: The moisture content is 0.1-0.34%.
6. The method for manufacturing a multi-layer container according to claim 1 or 2, wherein: The polyester resin is composed of structural units derived from diol and structural units derived from dicarboxylic acid, wherein 70 mol% or more of the structural units derived from dicarboxylic acid are derived from at least one selected from terephthalic acid and esters thereof, and 70 mol% or more of the structural units derived from diol are derived from ethylene glycol.
7. The method for manufacturing a multi-layer container according to claim 1 or 2, wherein: At least one of the polyamide resins is a non-crystalline resin.
8. The method for manufacturing a multi-layer container according to claim 1 or 2, wherein: The polyamide resin further includes amorphous polyamide resin, and the amorphous polyamide resin excludes the xylylenediamine-based polyamide resin. The ratio of the xylylenediamine polyamide resin to the amorphous polyamide resin is as follows: 60 to 95 parts by mass of the xylylenediamine polyamide resin and 40 to 5 parts by mass of the amorphous polyamide resin, excluding the xylylenediamine polyamide resin.
9. The method for manufacturing a multi-layer container according to claim 1 or 2, wherein: In the xylylenediamine-based polyamide resin, the α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 8 carbon atoms is adipic acid, and the aromatic dicarboxylic acid is isophthalic acid.
10. The method for manufacturing a multi-layer container according to claim 1 or 2, wherein: The method also includes the step of manufacturing the preform, including the step of adjusting the moisture content of the manufactured preform.
11. The method for manufacturing a multi-layer container according to claim 10, wherein: The manufactured preform is stored in a moisture-proof state to adjust the moisture content.
12. The method for manufacturing a multi-layer container according to claim 1 or 2, wherein: The preform further comprises a layer having a second polyester resin as a main component, The layer mainly composed of the polyester resin, the layer mainly composed of the polyamide resin, and the layer mainly composed of the second polyester resin are stacked in this order.
Citation Information
Patent Citations
Polyester laminated molded shape and use application thereof
JP1985232952A
Manufacture of multilayer stretch-molded vessel with intermediate layer arranged offset to inside surface side
JP1990229023A
Polyester resin structure for heating use
JP2006111718A
Multi-layer bottle
JP2007210209A
Multilayer container
JP2011037199A